Existence of Positive Solutions for Nonlinear Eigenvalue Problems. (8th March 2010) - Wang Wang, Sheng-Ping Sheng-Ping; Wong Wong, Fu-Hsiang Fu-Hsiang; Kung Kung, Fan-Kai Fan-Kai
Abstract : We use a fixed point theorem in a cone to obtain the existence of positive solutions of the differential equation, u ″ + λ f ( t, u ) = 0, 0 < t < 1, with some suitable boundary conditions, where λ is a parameter.